2019
DOI: 10.1080/15476286.2019.1593091
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hfq-binding RNAs in Caulobacter crescentus

Abstract: Small RNAs are important for post-transcriptional regulation of gene expression, affecting stability and activity of their target mRNAs. The bacterial Sm-like protein Hfq is required to promote pairing between both RNAs when their sequence complementarity is limited. To provide a first global view on the post-transcriptional landscape of the α-proteobacterium Caulobacter crescentus, we have identified the Hfq-binding RNAs employing High-throughput sequencing of RNA isolated by cross-linking immunoprecipitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Two trans-encoded sRNAs who can silence target mRNAs through base pairing were found to be slightly enriched in BR-bodies ( crfA 0.67 and chvR 0.27) (Frohlich et al, 2018; Landt et al, 2010), while another was found to be slightly depleted ( gsrN -0.24) (Tien et al, 2018). Pairing of sRNAs with mRNAs typically occurs through the Lsm protein Hfq (Santiago-Frangos and Woodson, 2018; Vogel and Luisi, 2011), and we observe that 252/257 of these RNAs that associate with Hfq (Assis et al, 2019) are enriched in BR-bodies (Table S1).…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…Two trans-encoded sRNAs who can silence target mRNAs through base pairing were found to be slightly enriched in BR-bodies ( crfA 0.67 and chvR 0.27) (Frohlich et al, 2018; Landt et al, 2010), while another was found to be slightly depleted ( gsrN -0.24) (Tien et al, 2018). Pairing of sRNAs with mRNAs typically occurs through the Lsm protein Hfq (Santiago-Frangos and Woodson, 2018; Vogel and Luisi, 2011), and we observe that 252/257 of these RNAs that associate with Hfq (Assis et al, 2019) are enriched in BR-bodies (Table S1).…”
Section: Resultsmentioning
confidence: 87%
“…While eukaryotic RNA silencing machinery is found in P-bodies and stress granules (Hubstenberger et al, 2017; Jain et al, 2016), sRNAs were found to be enriched in BR-bodies (Fig 3A) and are known to base pair with mRNAs often through the RNA chaperone Hfq (Santiago-Frangos and Woodson, 2018; Vogel and Luisi, 2011). Indeed, Hfq bound RNAs identified by HITS-CLIP (Assis et al, 2019) including both mRNAs and sRNAs are enriched in BR-bodies (Fig S6, Table S1), suggesting mRNA silencing may be influenced by BR-body localization. Cis-encoded asRNAs were also found to be enriched in BR-bodies (Fig 3) similar to stress granules where many short asRNAs associate through pairing to their complimentary mRNAs (Van Treeck et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…C. crescentus harbors many small regulatory RNAs (sRNAs) that can influence gene expression at the post-transcriptional level in a variety of ways, such as direct interaction with mRNAs [ 97 , 98 ]. Differential expression of sRNAs in response to Cu was observed in all conditions, except for SW cells in PYE.…”
Section: Resultsmentioning
confidence: 99%